Intrageneric structural variation in organelle genomes from the genus Dystaenia (Apiaceae): genome rearrangement and mitochondrion-to-plastid DNA transfer - Park, Seongjun; Park, SeonJoo (Frontiers in Plant Science, 2023)
During plant evolution, intracellular DNA transfer (IDT) occurs not only from organelles to the nucleus but also between organelles. To further comprehend these events, both organelle genomes and transcriptomes are needed. In this study, we constructed organelle genomes and transcriptomes for two Dystaenia species and described their dynamic IDTs between their nuclear and mitochondrial genomes, or plastid and mitochondrial genomes (plastome and mitogenome). We identified the putative functional transfers of the mitochondrial genes 5′ rpl2, rps10, rps14, rps19, and sdh3 to the nucleus in both Dystaenia species and detected two transcripts for the rpl2 and sdh3 genes. Additional transcriptomes from the Apicaceae species also provided evidence for the transfers and duplications of these mitochondrial genes, showing lineage-specific patterns. Intrageneric variations of the IDT were found between the Dystaenia organelle genomes. Recurrent plastid-tomitochondrion DNA transfer events were only identified in the D. takeshimana mitogenome, and a pair of mitochondrial DNAs of plastid origin (MIPTs) may generate minor alternative isoforms. We only found a mitochondrion-to-plastid DNA transfer event in the D. ibukiensis plastome. This event may be linked to inverted boundary shifts in its plastome. We inferred that the insertion region involved an MIPT that had already acquired a plastid sequence in its mitogenome via IDT. We propose that the MIPT acts as a homologous region pairing between the donor and recipient sequences. Our results provide insight into the evolution of organelle genomes across the family Apiaceae.삭제함: In addition, transcriptome analyses of the selected 36 Apicaceae species indicated that the gene transfer and duplication 37 events were lineage-specific. However, intrageneric variations of the 38 IDT were found between the Dystaenia organelle genomes.